COMPETITIVENESS OF THE TEXTILE AND CLOTHING INDUSTRY IN BULGARIA AFTER THE EU ACCESSION AND IN TIMES OF COVID-19 PANDEMIC - P. Zhelev (Trakia Journal of Sciences)
The purpose of this paper is to analyse the changes in Bulgaria’s competitiveness in the textile and clothing (T&C) industry after the European Union accession and in times of the coronavirus pandemic covering the period 2007-2020. In methodological terms the study uses various indicators including production value, employment, labour productivity, relative trade balance, revealed comparative advantage index, among others. Wherever possible the analysis is done in a comparative perspective benchmarking the performance of the sector in Bulgaria with that in Romania. The results show that the Bulgarian T&C industry has undergone a significant transformation in the last two decades increasing its productivity but being subject to significant jobs downsizing. While still competitive on the European market, with rising wages and production costs, the comparative advantages of the industry are gradually eroding. The coronavirus pandemic has hit the apparel subsector very hard while some textile producers which managed to shift their production to personal protective equipment items managed it successfully. However, this is a temporary solution. The T&C industry in Bulgaria is confronted with significant long-term challenges such as the green and the digital transformation, and the how it deals with them will determine the prospects of the sector.